Pain and modifiable risk factors among weight loss seeking Veterans with overweight. (1st September 2018) - Godfrey, Kathryn M.; Bullock, Anastasia J.; Dorflinger, Lindsey M.; Min, Kathryn M.; Ruser, Christopher B.; Masheb, Robin M.
Abstract: Objective: Overweight/obesity and chronic pain frequently co-occur and demonstrate a bidirectional relationship. Modifiable risk factors, such as eating behaviors and mental health symptoms, may be important to understand this relationship and improve interventions in Veterans. Design: Cross-sectional. Setting: Veterans Health Administration Medical Center outpatient clinic. Subjects: The sample of Veterans ( N  = 126) was mostly male (89.7%), White (76%), and non-Hispanic (94%) with average age of 61.9 years ( SD  = 8.5) and average body mass index (BMI) of 38.5 ( SD  = 7.5). Methods: Veterans referred for weight loss treatment (MOVE!) at VA Connecticut completed self-report questionnaires, and electronic medical records were reviewed. Results: Mean self-reported pain rating was 4.5 out of 10 ( SD  = 2.3). Moderate to severe pain was endorsed by 60% of the sample. Veterans with higher pain intensity and interference reported higher global eating disorder symptoms, emotional overeating, night eating, insomnia severity, and mental health symptoms (all p 's < 0.01). However, pain intensity and interference were not associated with BMI. Conclusions: For Veterans seeking behavioral weight loss treatment, higher pain intensity and interference were associated with more severe eating disorder, sleep, and mental health symptoms. A better description of the clinical characteristics of Veterans with pain who participate in MOVE! highlights their unique needs and may improve treatments to address pain in the context of weight loss treatment.